Inertia or Adaptability? The Effects of Outside Director Incumbency Capital on Incumbent Firms' Adoption of Discontinuous Technologies - Hensellek, Simon; König, Andreas; Graf-Vlachy, Lorenz; Szewczyk, Justin; Kurzhals, Christopher (Journal of Product Innovation Management, 2025)
We fuse research on incumbents' adaptation to discontinuous technologies with board capital theory to investigate how heterogeneity in incumbent firms' adoption of discontinuous technologies may be affected by what we label as outside director incumbency capital—the specific subset of social capital and human capital that outside directors possess due to their educational, professional, and social exposure to and entrenchment in the established technological paradigm. We predict two opposing effects: Outside director incumbency social capital will be positively associated and outside director incumbency human capital will be negatively associated with the speed and aggressiveness of discontinuous technology adoption. We further hypothesize that the two types of outside director incumbency capital interactively affect adoption speed and aggressiveness. We find support for most of our hypotheses in 1111 firm-year observations of 75 incumbent US retail firms and their adoption of e-commerce between 1995 and 2019. Our research offers partially counterintuitive insights into how outside directors' human and social capital differentially affect discontinuous technology adoption. Thereby, we add new facets to the research on incumbent heterogeneity and the emerging nuanced view of board capital, innovation, and firm adaptability. Altogether, bridging the strategic leadership perspective on incumbent heterogeneity and existing board-level research innovation, our study connects two important but previously disconnected conversations at the nexus of strategic leadership, governance, and innovation.
CRIS-Team Scopus Importer:2026-04-08
Keywords: adaptability; board capital; discontinuous technologies; outside directors